Influencia del Taller de Biodanza en el Desarrollo Social de los niños de 5 años de la I.E N°224 Indoamerica, Víctor Larco Herrera, 2017 - Agreda Gil, María Loren (2018)
The making of this research has been based on the bibliographic references of authors and web pages reviewed, also knowledge acquired during the academic years of our professional training._x000D_ This thesis was done with the purpose of determine the "Influence of biodanza workshop in social development of children of 5 years of EI No. 224 Indoamerica, Buenos Aires, Víctor Larco Herrera, 2017", with the main objective to help improving the social development in children of 5 years._x000D_ For this, the type of applied research has been considered, and we used the quasi - experimental design of two groups: control group and experimental group, with application of pretest and posttest for both groups, whose population was constituted by the children attending and enrolled. In the year 2017, obtaining a sample population in the yellow classroom (control group) of 10 children - 8 girls and orange classroom (experimental group) of 6 children - 12 girls._x000D_ The data collection instrument that was used to obtain improvements in children's social development was structured as follows: 2 dimensions (Individual and Group); each dimension had 2 indicators and 3 items for each indicator to evaluate, qualifying each with a point, in the end we obtained as a result that the level of development is as follows: From 0 to 4: start of social development, from 5 to 8: In process of social development and from 9 to 12: social development Achieved._x000D_ Therefore, it was concluded that the biodanza workshop did significantly influence the Social Development in children of 5 years of the I.E N ° 224 Indoamerica, Buenos Aires, Víctor Larco Herrera, 2017.